Réponses

  • Utilisateur Brainly
2013-11-09T13:59:26+01:00
1) (2y+3)(y-5)=2y(y-2)
2y²-7y-15=2y²-4y
-3y=15
y=-5

2) (2y-9)(8y-1)=(4y+3)²
16y²-70y+9=16y²+24y+9
-94y=0
y=0

3) (3y-1)(3y+1)=(9/2 y-1)(2y+4)

9y²-1=9y²+16y-4
16y=3
y=3/16
Meilleure réponse !
2013-11-09T14:01:27+01:00
(2y+3)(y-5)=2y(y-2)
2y²-10y+3y-15=2y²-4y
2y²-10y+3y-15-2y²+4y=0
-3y=15
y=-5

(2y-9)(8y-1)=(4y+3)²
16y²-2y-72y+9=16y²+24y+9
16y²-2y-72y+9-16y²-24y-9=0
-98y=0
y=0

(3y-1)(3y+1)=(9/2y-1)(2y+4)
9y²+3y-3y-1=9y²+18y-2y-4)
9y²-1-9y²-18y+2y+4=0
-16y+3=0
-16y=-3
y=3/16